TRPV4 receptor as a functional sensory molecule in bladder urothelium: Stretch‐independent, tissue‐specific actions and pathological implications. Issue 1 (21st November 2019) - Roberts, Max W. G.; Sui, Guiping; Wu, Rui; Rong, Weifang; Wildman, Scott; Montgomery, Bruce; Ali, Ahmed; Langley, Steve; Ruggieri, Michael R.; Wu, Changhao
Abstract: The newly recognized sensory role of bladder urothelium has generated intense interest in identifying its novel sensory molecules. Sensory receptor TRPV4 may serve such function. However, specific and physiologically relevant tissue actions of TRPV4, stretch‐independent responses, and underlying mechanisms are unknown and its role in human conditions has not been examined. Here we showed TRPV4 expression in guinea‐pig urothelium, suburothelium, and bladder smooth muscle, with urothelial predominance. Selective TRPV4 activation without stretch evoked significant ATP release—key urothelial sensory process, from live mucosa tissue, full‐thickness bladder but not smooth muscle, and sustained muscle contractions. ATP release was mediated by Ca 2+ ‐dependent, pannexin/connexin‐conductive pathway involving protein tyrosine kinase, but independent from vesicular transport and chloride channels. TRPV4 activation generated greater Ca 2+ rise than purinergic activation in urothelial cells. There was intrinsic TRPV4 activity without exogeneous stimulus, causing ATP release. TRPV4 contributed to 50% stretch‐induced ATP release. TRPV4 activation also triggered superoxide release. TRPV4 expression was increased with aging. Human bladder mucosa presented similarities to guinea pigs. Overactive bladders exhibited greater TRPV4‐induced ATP release with age dependence. These data provide the first evidence in humans for the key functional role of TRPV4 in urothelium with specific mechanisms and identify TRPV4 up‐regulation in aging and overactive bladders.